Evolving migraine management: Lithuania's telemedicine experience - Andruskevicius, Saulius; Petrosian, David; Dapkute, Austeja; Jokubaitis, Mantas; Ryliskiene, Kristina (Frontiers in Neurology, 2024)
Introduction COVID-19 challenges have underscored the potential of telemedicine in migraine management. This study focuses on assessing patients' telemedicine experience for headache management in Lithuania and identifying key barriers and facilitators for its wider use. Methods A nationwide e-survey was conducted in 2023 via the Lithuanian Association of Migraine Patients' website, social media platforms, websites of public and private healthcare facilities, and migraine self-help groups. The survey covered sociodemographics, migraine characteristics, previous experience with teleconsultations for headaches with neurologists and general practitioners (GP), perceived advantages and disadvantages of telehealth, and preferred future consultation types. Results Eight hundred and forty seven respondents with a confirmed migraine diagnosis were analyzed. The majority were female (97.2%), with a median age of 35 (IQR 30–42) years and an average of 5 (IQR 3–9) monthly headache days (MHDs). 7.0% of respondents had chronic migraine (CM). Prior teleconsultations for headaches were reported by 35.2% of respondents, 26.2% with a GP and 17.0% with a neurologist (p < 0.0001). Teleconsultation outcomes included continuation of a prescribed treatment (84.7% for GPs and 83.3% for neurologists, p = 0.7295), initiation of new acute medications (12.2% for GPs with 70.4% reported as effective and 27.1% for neurologists with 84.6% effective, p = 0.0005 and p < 0.0001, respectively). Reasons for not undergoing remote neurology consultations: the lack of inquiry (69.7%), unavailability from neurologists (18.1%) and respondent's opposition to remote consultations (12.2%). Patients evaluated their experience with remote neurology services better than that of GPs (p = 0.0289). 67.3% of respondents preferred a mixed-mode approach for future consultations. In-person-only preference (29.0%) correlated with multiple factors, including history of remote primary neurology consultations (OR 5.89, p = 0.0022), lower education (OR 2.20, p = 0.0001), physically demanding work (OR 1.95, p = 0.0001), and number of drawbacks in telemedicine identified (OR 1.30, p < 0.0001), and worse experience of a prior remote GP consultation (OR 0.704, p < 0.0001). The main indicator of preference for remote-only consultations was the perception of fewer telemedicine disadvantages (OR 0.503, p = 0.0007). Conclusions Our findings confirm that telemedicine contributes to effective migraine management and is used limitedly in Lithuania. Despite one-third of respondents having experienced teleconsultations, significant barriers remain. Our study highlights a clear preference for a hybrid consultation type.